You are on page 1of 5

# Simultaneous Equations and Quadratic Formula Test

Time: 30 minutes
Marks: 29

Name:

## Complete the following questions on a piece of paper.

Question 1
Solve the simultaneous equations by using the elimination method.
1. 3x + 4y = 17
6x + y = 20



2. 2x + 3y = 14
3x + 2y = 11



3. 4x + 3y = 26
3x - 5y = -24



4. 4x - 3y = 2
5x + 7y = -19



Question 2
1. x2 + 9x + 4=0
2. 2x2 + 3x - 7 = 0
3. 9x2 + 5x - 2 = 0





How do you feel you did in the test? Tick the box which best represents you.
Test was easy
Test was fine. I know I passed
I did not pass
If you think you did not pass, what do you think you can do next time to be more prepared?
________________________________________________________
________________________________________________________
________________________________________________________
________________________________________________________

Question 1
1. 3x + 4y = 17
6x + y = 20
We need to make the coefficients of one of the variables (either x or y) the same in both equations. We can
make the coefficients of x the same by multiplying the first equation by 2.Doing this we get:

6x + 8y = 34
6x + y = 20

Now that the coefficients of x are the same, we can now subtract these two equations. Doing this we get:
7y = 14
Solving for y (by diving both sides by 7) we get:
y = 2
Now we take this value of y and substitute it into either one of our original equations and then solve for x.
Subbing this value into our first equation we get:
3x + 4y = 17
3x + 4(2) = 17
3x = 9
x = 3

(divided by 3)

## So our values are x=3and y=2.

2. 2x + 3y = 14
3x + 2y = 11
We need to make the coefficients of one of the variables (either x or y) the same in both equations. We can
make the coefficients of x the same by multiplying the first equation by 3 and the second one by 2.Doing
this we get:
6x + 9y = 42
6x + 4y = 22

Now that the coefficients of x are the same, we can now subtract these two equations. Doing this we get:
5y = 20
Solving for y (by diving both sides by 5) we get:
y = 4
Now we take this value of y and substitute it into either one of our original equations and then solve for x.
Subbing this value into our first equation we get:

2x + 3y = 14
2x + 3(4) = 14
2x = 2
x = 1

(divided by 2)

## So our values are x=1 and y=4.

3. 4x + 3y = 26
3x - 5y = -24
We need to make the coefficients of one of the variables (either x or y) the same in both equations. We can
make the coefficients of x the same by multiplying the first equation by 3 and the second one by 4.Doing
this we get:

12x + 9y = 78
12x - 20y = -96

Now that the coefficients of x are the same, we can now subtract these two equations. Doing this we get:
29y = 174
Solving for y (by diving both sides by 29) we get:
y = 6
Now we take this value of y and substitute it into either one of our original equations and then solve for x.
Subbing this value into our first equation we get:
4x + 3y = 26
4x + 3(6) = 26
4x = 8
x = 2

(divided by 2)

## So our values are x=2 and y=6.

4. 4x - 3y = 2
5x + 7y = -19
We need to make the coefficients of one of the variables (either x or y) the same in both equations. We can
make the coefficients of x the same by multiplying the first equation by 3 and the second one by 4.Doing
this we get:
20x - 15y = 10
20x + 28y = -76

Now that the coefficients of x are the same, we can now subtract these two equations. Doing this we get:
-43y = 86
Solving for y (by diving both sides by 13) we get:

y = -2
Now we take this value of y and substitute it into either one of our original equations and then solve for x.
Subbing this value into our first equation we get:
4x - 3y = 2
4x - 3(-2) = 2
4x =-4
x = -1

(divided by 2)

## So our values are x=-1 and y=-2.

Question 2
2

1. x + 9x + 4=0
In this case we have a=1, b=9 and c=4.
So using our formula:

x=

b b24 ac
2a

( 9 ) ( 9 ) 4 ( 1 )( 4 )
x=
2( 1)
2

x=

( 9 ) 65
2(1)

x=

( 9 )+ 65
2 (1)

= -0.47

Or

x=

( 9 ) 65
2(1)

= -8.53

## (One mark awarded for correct substitution of values into formula)

2

2. 2x + 3x - 7 = 0
In this case we have a=2, b =3 and c = -7.
So using our formula:

x=

b b24 ac
2a

( 3 ) ( 3 ) 4 ( 2 ) (7 )
x=
2 (2)
2

x=

( 3 ) 65
2(2)

x=

( 3 ) + 65
2 (2)

Or

= 1.27

x=

( 3 ) 65
2(2)

= -2.77

## (One mark awarded for correct substitution of values into formula)

2

3. 9x + 5x - 2 = 0
In this case we have a=9, b =5 and c = -2.
So using our formula:

x=

b b24 ac
2a

( 5 ) ( 5 ) 4 ( 9 )(2 )
x=
2( 9)
2

x=

( 5 ) 97
2(9)

x=

( 5 ) + 97
2 (9)

= 0.27

Or

x=

( 5 ) 97
2(9)
= -0.82